Phenotype to genotype and back in emerging and established crop species - Woods, Patrick O'Neal David, author; McKay, John, advisor; Hufbauer, Ruth, committee member; Funk, Chris, committee member; Sloan, Dan, committee member (Colorado State University. Libraries, 2023)
Understanding the relationship between the phenotype and genotype is a fundamental goal of genetics. Through the years, two primary approaches have been developed for studying the phenotype-genotype relationship: forward genetic and reverse genetics. Forward genetics enables the potential discovery of numerous candidate genes controlling a phenotype while reverse genetics allows for the mechanistic validation of a single gene's role in controlling a phenotype. Applying these two approaches to crops enables the discovery of genetic targets that can be used for crop improvement through breeding. In this dissertation, I focused on understanding the phenotype-genotype relationship in both the emerging crop Cannabis sativa and the established crop Maize. In Chapter 1, I used both a forward a reverse genetics approach to identify and validate candidate genes controlling agriculturally important traits (agronomic and biochemical) in Cannabis sativa. In Chapter 2, I used a reverse population genetics approach to identify the genetics underlying local adaptation in feral and domesticated populations of Cannabis sativa. In Chapter 3, I used a forward genetics approach to identify candidate genes controlling variation in root system architecture in Maize. Collectively, this work demonstrates how modern genomic techniques can be applied to both new and old crop systems to identify genetic targets for use in crop innovation through breeding.